UPAYA PENCEGAHAN STUNTING MELALUI OPTIMALISASI PENGOLAHAN PRODUK LOKAL SEBAGAI SUMBER NUTRISI BALITA - Qisma Ziyan Farkha; Ries Dyah Fitriyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research explores efforts to overcome stunting in Probolinggo Regency, East Java, which has a stunting prevalence of 12.97% in 2023. Research in Banyuanyar Kidul Village focuses on socialization and demonstration of making MPASI from corn, as a local village asset. Involving 145 mothers and toddlers from four posyandu. This outreach activity is a form of education and demonstration carried out with the theme